Hubungan Penyajian Informasi Pembangunan Infrastruktur dengan Perilaku Pencarian Informasi Followers - Yudha Ari Azhar; Anne Ratnasari (UNISBA Press, 2023)
Abstract. Information search behavior that changes with the changing times with the media that continues to grow. The isntagram account @dsdadbmkotabdg be an option in obtaining information on the infrastructure development of Bandung City. The purpose of this study was to determine the relationship between the presentation of information in the type of information, the attractiveness of information, and the style of messages on @dsdadbmkotabdg Instagram account with the behavior of information seekers followers of infrastructure development in the city of Bandung. The theory used in this study is the Theory of Information Integration. This study used quantitative research methods, with a correlational approach. Data collection by distributing questionnaires to respondents. The population in this study is 1.153 followers of @dsdabmkotabdg Instagram accounts who liked Instagram posts in February 2023. From calculations using the Slovin formula, the number of samples that must be taken in this study is 93 respondents. The result of this study is that there is a strong relationship between the presentation of information on the development, maintenance, and inauguration of infrastructure with information seeking behavior. Abstrak. Perilaku pencarian informasi yang berubah-ubah seiring perubahan zaman dengan media yang terus berkembang. Akun isntagram @dsdadbmkotabdg menjadi pilihan dalam mendapatkan informasi pembangunan, pemeliharaan, dan peresmian infrastruktur Kota Bandung. Tujuan penelitian ini dilakukan untuk mengetahui hubungan penyajian informasi dalam jenis informasi, daya tarik informasi, dan gaya pesan pada akun Instagram @dsdadbmkotabdg dengan perilaku pencari informasi followers. Teori yang digunakan dalam penelitian ini yaitu Teori new media. Penelitian ini menggunakan metode penelitian kuantitatif, dengan pendekatan korelasional. Pengumpulan data dengan menyebarkan kuesioner kepada responden. Populasi dalam penelitian ini adalah followers akun Instagram @dsdabmkotabdg sebanyak 1.153 yang menyukai postingan instagram pada Februari 2023 . Dari perhitungan menggunakan rumus Slovin maka jumlah sampel yang harus diambil dalam penelitian ini sebanyak 93 responden. Hasil dari penelitian ini adalah terdapat hubungan yang sangat kuat antara penyajian informasi pembangunan, pemeliharaan, dan peresmian infrastruktur dengan perilaku pencarian informasi followers.